(untitled) (Research, Society and Development, 2020)
This work sought to analyze and compare the production and activities of family farming, based on the results of the last two agricultural censuses (2006 and 2017). In the methodological procedures, bibliographic research and document analysis were used. Among the results, it is postulated that family farming in the state of Maranhão is marked by temporary crops with emphasis on cassava. The data from the Census of Agriculture point to a low participation of family farming in agricultural production. The justification is that most of the production units have low technological standards and use production for their own subsistence.